Evolution of an Airy pulse energy flow induced by a dielectric plane boundary - Kuryzheva, O. V.; Nerukh, A. G. (CAOL, 2016)
Transformation of energy flows of an electromagnetic Airy pulse by a plane boundary of a dielectric is considered. It is shown that a problem formulation is equivalent to a case of a permittivity sharp change in a half space at zero moment of time. It allows to use the resolvent method for solution of the Volterra integral equation describing the phenomenon. Explicit expressions for transmitted and reflected pulses are obtained and energy flows are analyzed.
Keywords: electromagnetic Airy pulse; dielectric inhomogeneity; Volterra integral equation